Vaccine hesitancy among parents of children with chronic diseases of different pathophysiology: a cross-sectional study in Sivas, Türkiye - Ayça Kömürlüoğlu; Nurullah Çelik; Ayla Uzun Çiçek; Siddika Songül Yalçın (BMC Public Health)
Abstract Background Vaccine hesitancy (VH) and vaccine refusal are increasing globally, posing a significant challenge to public health. This study aimed to evaluate VH and associated factors in parents of children with different chronic conditions, comparing them to a control group of healthy children. Methods This cross-sectional study included mothers of children aged 6 to 12 years, diagnosed with Autism Spectrum Disorder (ASD), attention deficit hyperactivity disorder (ADHD), type 1 diabetes mellitus (T1DM), congenital heart disease (CHD), congenital hypothyroidism (CH) and Familial Mediterranean Fever (FMF) and healthy children without chronic diseases. The study collected sociodemographic data, and parents completed the Parent Attitudes about Childhood Vaccines (PACV) survey and the Parental Attitude Research Instrument (PARI). Vaccine hesitancy was defined as a PACV score ≥ 50. Results A total of 1163 participants were included, consisting of 546 children with chronic conditions. The overall VH rate was %14.7. Compared to control group, parents of children with T1DM had 3.3 times higher odds of VH, and parents of children with ASD had 1.8 times higher odds of VH. However, parents of children with CHD had lower odds of VH [OR: 0.38 (95% CI: 0.15–0.97)]. The most common reasons for VH were concerns about vaccine ingredients (40.2%) and fear of adverse events (22.5%). The primary suggested solution was receiving more information from healthcare professionals (33.3%). Factors such as having a child with a chronic condition, personal experience with vaccine adverse events, and reliance on the internet for vaccine information were associated with increased VH, whereas obtaining information from healthcare professionals was linked to lower VH. Higher parental democratic attitudes were associated with lower VH, while increased marital conflict was linked to higher VH. Conclusion Addressing both informational gaps and psychosocial factors, such as marital conflict and democratic parenting attitudes, can enhance vaccine acceptance. Healthcare professionals should provide personalized guidance and resources to empower parents, enabling them to make informed vaccination decisions for high-risk groups such as children with chronic conditions.